ANALISIS PERENCANAAN PAJAK MELALUI PENYUSUTAN AKTIVA TETAP DAN PERHITUNGAN PAJAK BADAN PDAM TIRTA JENEBERANG KABUPATEN GOWA - Andi Arifwangsa; Saida Said; Ulfa Husain (Jurnal Riset Perpajakan: Amnesty, 2019)
In this research aims to whether with tax planning through the depreciation of fixed assets on the company can minimize the tax burden. This research uses a secondary method on the PDAM Tirta Jeneberang Regency Gowa.  Data used in this research is data on the annual report of the PDAM Tirta Jeneberang Regency Gowa. Data collection is done by collecting financial report data in the company year that is a sample of the research of PDAM company Tirta Jeneberang Kabupaten Gowa. The Data is collected by conducting a documentation method.  From the analysis conducted on the implementation of tax planning applied by the company with the prevailing taxation law apparently the company does not commit violations and still follow all applicable regulations.